Indigenous and minor vegetables of North-East India - Das, Biswajit; Kandpal, B. K.; Devi, H Lembisana; Singh, Satyapriya (Indian Horticulture, 2020)
North eastern region of India is rich in biodiversity of flora and fauna. Apart from major vegetables which are indigenous to this region, there are diversified traditional plants which are consumed as ethnic foods. Conservation and documentations of all these major and minor vegetables is very much essential.